Calcium-related Neurotoxicity of Oxaliplatin: Understanding the Mechanisms to Drive Therapy - Marmiroli, Paola; Cavaletti, Guido; Carozzi, Valentina; Riva, Beatrice; Lim, Dmitry; A. Genazzani, Armando (Current Medicinal Chemistry, 2015)
Oxaliplatin is one of the most widely used anticancer drugs representing the cornerstone of the treatment of colorectal cancer. Yet a number of side effects, including oxaliplatin- induced peripheral neurotoxicity (OIPN) which represents a dose-limiting side effect in the clinical use of oxaliplatin, limit its use and a better understanding of its pathogenesis would offer a great opportunity to improve the “quality of survival” of cancer patients. So far, no treatment able to prevent or limit OIPN has been approved, and one of the reasons for this unmet clinical need is the incomplete knowledge of its pathogenesis preventing the development of rationalebased pharmacological interventions. Preclinical and clinical evidence raised the hypothesis that intracellular calcium-related events might play an important role in the onset of OIPN. Yet, the results of mechanistic pre-clinical studies appear inconsistent and, therefore, their relevance in neuroprotective drugs design is still uncertain. Indeed, it is at present unclear whether aberrant calcium signalling is the key pathogenetic moment or whether it just constitutes the mediator of the clinical phenotype. This review will summarize the preclinical results involving calcium-related events and OIPN with the aim to provide an updated overview of the available evidence and highlight the most promising strategies to design effective neuroprotective drugs. In particular, we will focus on the pre-clinical evidence suggesting that TRPV1, TRPM8 or TRPA1 might be involved, as these appear particularly amenable to pharmacological modulation.
Keywords: in vitro